Evaluation of Two Rotary Nickel-Titanium Systems for Gutta Percha Removal during Endodontic Retreatment - Nawal A Al-Sabawi (University of Mosul, College of Dentistry, 2013)
Aims: The purposes of this study were to evaluate the efficacy of two rotary systems (RaCe and ProTaper) compared with hand files, in the removal of gutta percha during retreatment. Retreatment time, amount of apically extruded debris, and procedural errors were also evaluated. Materials and Methods: Forty extracted mandibular premolars were instrumented to size 30 and obturated with lat-eral condensed gutta percha. Then teeth were randomly divided into four groups, 10 teeth each. Re-moval was performing with chloroform and one of the following techniques: (I) Hedstrom and K-files, (II) Hedstrom and hand ProTaper, (III) Rotary ProTaper, and (IV) RaCe. Retreatment times, apically extruded debris, and broken instrument were recorded. The root split longitudinally viewed under ste-reomicroscope at (10 X) photograph are taken, and then the area of remaining filling material and whole area of the canal were measured using SigmaScan software. Data were analyzed statistically using one way ANOVA and Tukey test. Results: The two rotary systems left significantly less remain-ing filling material, faster, and produce less amount of apically extruded debris compared to hand files. There was no significant difference between the two rotary systems, but there was significant differ-ence between the two hand files regarding the amount of remaining filling materials. Only RaCe exhib-its no fracture instruments during retreatment. Conclusions: The two rotary systems were found to be effective and faster in removing gutta percha during endodontic retreatment.